2020
DOI: 10.1155/2020/5686029
|View full text |Cite
|
Sign up to set email alerts
|

Pentagalloyl Glucose‐ and Ethyl Gallate‐Rich Extract from Maprang Seeds Induce Apoptosis in MCF‐7 Breast Cancer Cells through Mitochondria‐Mediated Pathway

Abstract: Bouea macrophylla Griffith, locally known as maprang, has important economic value as a Thai fruit tree. The maprang seed extract (MPSE) has been shown to exhibit antibacterial and anticancer activities. However, the bioactive constituents in MPSE and the molecular mechanisms underlying these anticancer activities remain poorly understood. This study aims to identify the active compounds in MPSE and to investigate the mechanisms involved in MPSE-induced apoptosis in MCF-7 treated cancer cells. The cytotoxic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…MPSE treatment further increased IR-induced DNA-DSBs, as we observed an increase in γH2AX expression and the presence of γH2AX foci in the combination treatment group. A previous study showed that MPSE promotes intracellular reactive oxygen species (ROS) production and prevents cell cycle progression, leading to inhibition of proliferation and apoptosis induction in breast cancer MCF7 cells [ 14 ]. Our results suggested that pre-treatment with MPSE triggers ROS overproduction in IR-treated cells and enhances the effect of radiation on breast cancer cells via increasing IR-induced DNA damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MPSE treatment further increased IR-induced DNA-DSBs, as we observed an increase in γH2AX expression and the presence of γH2AX foci in the combination treatment group. A previous study showed that MPSE promotes intracellular reactive oxygen species (ROS) production and prevents cell cycle progression, leading to inhibition of proliferation and apoptosis induction in breast cancer MCF7 cells [ 14 ]. Our results suggested that pre-treatment with MPSE triggers ROS overproduction in IR-treated cells and enhances the effect of radiation on breast cancer cells via increasing IR-induced DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that MPSE induced apoptosis in breast cancer cells via the mitochondrial pathway [ 14 ]. In this study, we found that the combined treatment of MPSE and IR markedly increased the apoptotic effect in breast cancer cells compared with a single treatment of IR or MPSE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, consistent with our findings, previous studies undertaken using cell cultures, as we did, have shown that pentagalloylglucose could be involved in eliciting anti-cancer effects through mechanisms including pro-apoptosis, anti-proliferation, anti-angiogenesis, anti-metastasis and inhibition of glycoprotein [ 28 ]. Besides, Kantapan et al [ 29 ] recently reported that extracts containing pentagalloylglucose could promote intracellular ROS production and induce apoptosis in cancer cells, although it was not demonstrated whether those effects could be solely or partly attributed to the presence of pentagalloylglucose, as two other constituents were found to be present in the extract. Lin et al [ 30 ], who used cultured cells (HepG2, 293T, HEp-2, MRC-5) grown and treated in conditions very similar to ours (DMEM supplemented with 10% fetal calf serum, 24 h treatment, MTT assay), showed pentagalloylglucose lacked toxicity to the cells up to 50 μM but did not investigate higher concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies revealed that MPSE contains high amounts of active compounds such as 1,2,3,4-6-pentyl-O-galloyl-β-D-glucose (PGG), ethyl gallate (EG), and gallic acid (GA). MPSE induces increases in intracellular reactive oxygen species (ROS) and subsequently induces cell cycle arrest and apoptosis in human breast cancer cells [16]. A main active compound found in MPSE, PGG has been extensively studied for its anti-cancer properties.…”
Section: Introductionmentioning
confidence: 99%